Keloid Multipel Besar pada Perempuan Asia Muda - Tanjung, Setia Yuda Nugraha (PT Kalbe Farma Tbk., 2023)
The abnormal skin wound healing process in the formation of dense fibrous tissue with excessive growth is known as a keloid. Genetic, systemic, and local factors are associated with keloid formation. Large and multiple keloids in various areas of the body are rarely reported. This article reports a case of large multiple keloids in a young Asian woman was reported. Setia Yuda Nugraha Tanjung. Large Multiple Keloid in a Young Asian Woman.